UJI AKTIVITAS ANTIDIABETES EKSTRAK DAUN SENGGANI (Melastoma malabathricum L.) SECARA IN VITRO DENGAN METODE PENGHAMBATAN ?-GLUKOSIDASE - Munawarohthus Sholikha; Muhammad Fathi (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Diabetes mellitus is a disorder of the metabolism of fat, carbohydrate, and protein due to defectsin insulin secretion, insulin sensitivity or both. In 2017, diabetics in Indonesia has reached 10.3million of 8.5 % prevalence and it was estimated to reach 16 million in 2023. The inhibition of?-glucosidase is thought to be effective in delaying the breakdown of carbohydrates in theintestine and can lower blood glucose levels in diabetic patients. One of the mechanisms ofdiabetes treatment is to inhibit ? -gucosidase. Empirically, senggani leaves commonly used totreat infections, high blood pressure and diabetes. This research aims to obtain an extract fromsenggani leaves (Melastoma malabathricum L.) on the inhibition of the ?-glucosidase andidentify compounds that contained in the sample. The simplisia powder from senggani leaveswas extracted by maceration and reflux techniques using ethanol 96%. The antidiabetic activityessay of senggani leaves was read using a microplate reader at a wavelength of 410 nm. Theresult showed that the ethanol extract of senggani leaves from the maceration technique hadinhibition with IC50 is 879.559 ?g/ml and from reflux techniques with IC50 values of 1061.631?g/ml. Phytochemical constituent in both extract senggani leaves are flavonoids, tannins,saponins, and alkaloids